Hubungan Pengetahuan dan Sikap Keluarga dengan Kesiapsiagaan Menghadapi Risiko Gempa Bumi dan Tsunami di RW 03 Kelurahan Purus Tahun 2023 - Muhammad Rizki Setyawan; Reflita Reflita; Tasman Tasman; Rachmadanur Rachmadanur; Verra Widhi Astuti (Jurnal Keperawatan Sehat Mandiri, 2023)
Purus Urban Village is an area located on the coast of Padang City which is classified as a red zone, having a high tsunami landfall. Based on an initial survey, 2 out of 3 heads of households stated that they did not know the actions before and after an earthquake and tsunami, and would not plan evacuation drills for the family at home. This study aims to determine the relationship between family knowledge and attitudes with earthquake and tsunami risk preparedness. Cross-sectional research design, research conducted in RW 03 Purus Village from November 2022 to May 2023. The study population was all heads of families in RW 03 Purus Village with simple random sampling a sample size of 120 families. Data collection techniques using questionnaires. Univariate data analysis by means of descriptive statistics in the form of frequency distribution and percentage, bivariate analysis by means of Chi-Square statistical test. The results showed that almost half of the (49.2%) had low preparedness, (7.5%) had low knowledge and more than half of the (50.8%) had negative attitudes. There was a significant relationship between knowledge and preparedness with a significance value (p-value) = 0.033 and a significant relationship between attitude and preparedness with a significance value (p-value) = 0.044. It is recommended that urban village increase the knowledge, attitudes and preparedness of families by promoting socialization or counseling and developing community action plans through earthquake and tsunami disaster preparedness groups. Future researchers should examine the factors that influence family preparedness in facing the risk of earthquake and tsunami disasters.